1961
DOI: 10.1017/s0021859600023911
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time of application of phosphate and potash on sugar beet

Abstract: 1. Twenty-nine experiments on sugar beet in 1957–59 compared ploughing-down of phosphate and potash in the previous autumn with spring application before the seed-bed preparations.2. On average, spring application gave a higher yield of sugar and tops than ploughing-down, both in the wet summers of 1957 and 1958 and in the dry summer of 1959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1962
1962
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…Planning and supervision of the experiments The early experiments, co-ordinated by Crowther, was similar to that described by Boyd et al (1970), were reported by Boyd, Garner & Haines (1957) harvesting procedure was described by Adams and the later experiments, summarized in this (1962) and beet analyses by Tinker (1965). Except paper, were reported by Adams (1961aAdams ( , b, 1962, series I which compared autumn and spring Tinker (1965Tinker ( , 1970, Draycott (1969Draycott ( , 1971 and fertilizer dressings, all results are from spring Draycott & Durrant (1969). Our object in bringing dressings.…”
Section: Introduction Experimentsmentioning
confidence: 88%
“…Planning and supervision of the experiments The early experiments, co-ordinated by Crowther, was similar to that described by Boyd et al (1970), were reported by Boyd, Garner & Haines (1957) harvesting procedure was described by Adams and the later experiments, summarized in this (1962) and beet analyses by Tinker (1965). Except paper, were reported by Adams (1961aAdams ( , b, 1962, series I which compared autumn and spring Tinker (1965Tinker ( , 1970, Draycott (1969Draycott ( , 1971 and fertilizer dressings, all results are from spring Draycott & Durrant (1969). Our object in bringing dressings.…”
Section: Introduction Experimentsmentioning
confidence: 88%
“…N per acre was significantly associated with a smaller plant population (r -+ 0-71) but the effects were not significant in other years. Factors which affect plant population presumably operate before singling time and there is some British (Adams, 19616) and much German (Fischnich, Grimm & Thielebein, 1959) evidence that nitrogen depresses seedling emergence. Warren & Johnston (1960) have also shown that broadcast dressings of nitrogen and potash fertilizers check germination and retard growth of sugar beet seedlings.…”
Section: Responses Without Farmyard Manurementioning
confidence: 99%
“…Russell (1956), and Draycott et al (1975Draycott et al ( , 1976 obtained some benefit from application in autumn before ploughing. Conversely, Adams (1961), Webber (1961), Holmes et al (1973), Last & Draycott (1977) and Clare & Harrod (1978) showed small benefits from seedbed applications. In the remaining studies there was essentially no difference between treatments.…”
Section: Sugar Yield and Sugar Concentrationmentioning
confidence: 99%
“…recommendations for these nutrients are, in part, To try to reconcile these conflicting data it was based upon conflicting evidence. For instance, Webber decided to conduct a new series of experiments, using (1961) and Adams (1961) obtained beneficial re-modern varieties and management techniques, to study the interaction of soil type, time of fertilizer application and weather patterns on the yield and processing quality of sugarbeet in England.…”
Section: Time Of Application and Chemical Form Of Potassiummentioning
confidence: 99%
See 1 more Smart Citation